A debreceni KLTE archontológiája II. Matematikai Intézet (1950–1990) - Mudrák, József (Gerundium, 2014)
ARCHONTOLOGY OF THE KOSSUTH UNIVERSITY OF DEBRECEN 1950–1990 2. PART. INSTITUTE OF MATHEMATICS. he archontology of the Faculties of the Natural Sciences and the central units of the Kossuth University between January 1, 1950 – December 31 was prepared on the basis of the personal documents of the Human Resources of the Rectorate supplemented by the chronological documents of the Human Resource Department. he existing documents are not complete, therefore the archeontology cannot be drawn up completely. he second part introduces the teaching and administrative staf of the Institute of Mathematics in chronological order including everybody from the head of the institute to the administrator.